Tunable Few-optical-Cycle Pulses by Group-velocity-matched OPAs - Cerullo, Giulio; Manzoni, Cristian; Brida, Daniele (My University, 2015)
We review our work on the development of ultra-broadband OPAs. By group-velocity matching between signal and idler waves, we generate pulses with duration of few optical cycles and tunability from the visible to the infrared.
Keywords: 530